Pacing strategies of 10 km elite open water swimmers with enhanced temporal resolution: World Swimming Championships Budapest 2022 - Fernández-Asensio, J. M.; Rodríguez-Adalia, L.; Hermosilla-Perona, F.; Chaverri, D.; Veiga, S. (Journal of Sports Sciences, 2024)
The pacing and tactical race strategies of open water (OW) swimmers have been recognized as significant performance determinants in these events, despite the limited resolution of available race data due to the aquatic environment constraints. The main objective of the study was to re-examine the pacing strategies and race tactics of elite OW swimmers from new enhanced temporal resolution data during the 2022 World Championships (WCH). Data were collected from 58 males and 58 females participants classified into 5 performance groups (G1-G5) depending on their finishing positions. Average velocity, stroke rate, and partial positions were obtained for each swimmer in 17 timing points over the 10 km race (on average 550 m or 5.5% of the race distance). The pacing strategies of successful swimmers, especially men, showed a less conservative behaviour than previous WCH with leading race positions (at least top-6) from the race early stages and a lower race density (˜2%) upon arrival. The enhanced temporal resolution race data showed greater pacing variations as well as end race spurts over a shorter distance than previously reported for successful competitors. These results describe a partly new paradigm in OW race strategies compared to previous race data with low temporal resolution.